PERANCANGAN SISTEM KERJA BAGIAN CUSTOM CLEARANCE PT. GEX DENGAN METODE WORK LOAD ANALYSIS - DANAR SAPUTRA; BASUKI ARIANTO BASUKI ARIANTO; W. TEDJA BHIRAWA (JURNAL TEKNIK INDUSTRI, 2020)
ABSTRACT PT. GEX is a company engaged in export and import services. at this time the systemof division of labor was not made properly which resulted in several problems in shippingcontainers. some employees often get very heavy workloads that result in late containerspending. this problem will be analyzed using the work load analysis method. Based on theresults of observation data on pt. gex will be calculated using the work load analysis method.The results of data analysis that have been processed are known to be at the initialoperational conditions of input productive percentage of 66% and non-productive 34%,operational output 70% and 30%, and operational finishing 68% and 32%. After analysisbecame operational input 79.53%, operational output was 86.10%, operational finishing was83.64%. This custom clearance operational analysis shows that the result is less training byPT. GEX thus causing a delay in the shipping process.Key Word : Work Load Analysis (WLA), sistem kerja, custom clearance